2014
DOI: 10.2166/nh.2014.016
|View full text |Cite
|
Sign up to set email alerts
|

Forest disturbance effects on snow and water yield in interior British Columbia

Abstract: Long-term studies at Mayson Lake (ML) and Upper Penticton Creek (UPC) in British Columbia's southern interior quantify snow-dominated hydrologic response to natural disturbances and logging. Following natural disturbance at ML, changes in snow accumulation related directly to mountain pine beetle attack were measurable by the fifth year following attack, when canopy transmittance had increased 24% due to needlefall. In year 1, April 1 snow water equivalent (SWE) was 48% higher in the clearcut than in the pine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…The decreasing importance of snow interception after spruce forest defoliation was proven in our study, which corresponds to results reported by Pugh and Small (2013) from the western United States. Our results also correspond to conclusions presented by Winkler et al (2015) who used both measured shortwave radiation and hemispherical photographs to derive the canopy transmittance. However, the reliability of results from the Ptaci Brook catchment could be influenced by the fact that our sampling sites are mostly in disturbed forests with dense treetops, and thus there is still a relatively big amount of snow intercept by the canopy formed by small branches.…”
Section: Vegetation Structure and Its Possible Impact On Runoffsupporting
confidence: 90%
See 1 more Smart Citation
“…The decreasing importance of snow interception after spruce forest defoliation was proven in our study, which corresponds to results reported by Pugh and Small (2013) from the western United States. Our results also correspond to conclusions presented by Winkler et al (2015) who used both measured shortwave radiation and hemispherical photographs to derive the canopy transmittance. However, the reliability of results from the Ptaci Brook catchment could be influenced by the fact that our sampling sites are mostly in disturbed forests with dense treetops, and thus there is still a relatively big amount of snow intercept by the canopy formed by small branches.…”
Section: Vegetation Structure and Its Possible Impact On Runoffsupporting
confidence: 90%
“…However, field data bridge the gap between the real physical process and its conceptualization using suitable equation and parameters. Based on measured or simulated data, it is possible to estimate the effect of forest disturbances on snowmelt dynamics, such as windstorms, fires and insect attacks (Burles and Boon, 2011;Pomeroy et al, 2012;Pugh and Small, 2013;Winkler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Following the extensive logging over half of the upper elevations of the watershed, melt in south-facing upper clear-cuts became synchronized with melt from the lower elevation forest, as described in Winkler, Spittlehouse, Boon, and Zimonick (2015), further advancing the timing, and increasing the magnitude, of high spring flows. This effect is corroborated by modelling work by Schnorbus and Alila (2013), who also showed earlier melt and increased runoff from highelevation clear-cuts augmenting that from lower elevations to produce higher peak flows.…”
Section: Changes In Daily Yield and Daily Flow Durationmentioning
confidence: 92%
“…As is typical of snowmelt‐dominant regions of the Pacific Northwest, the highest flows occur during the snowmelt freshet between April and June, followed by a general recession through summer and the following winter, with occasional increases in streamflow associated with autumn rainstorms. The soils in the Upper Penticton Creek catchments are generally less than 2‐m thick and consist of sandy loam and loamy sand that overlie glacial till and granitic rocks (Winkler, Spittlehouse, Boon, & Zimonick, ). Rainbow trout ( Oncorhynchus mykiss ) has been observed throughout the Upper Penticton Creek watershed.…”
Section: Methodsmentioning
confidence: 99%